(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Neonatal intestinal obstruction is the commonest surgical emergency in neonatal period. The outcome in neonatal intestinal obstruction has improved dramatically due to the improvements in diagnostic facilities and neonatal intensive care, and surgical advances. Objective: To detect the pattern of neonatal intestinal obstruction, to find out their cause and outcome after management. Materials and Methods: This was a 10 years retrospective review of all children aged 28 days and below, managed for intestinal obstruction between March 2006 and February 2016 at the Pediatric Surgical Division of Combined Military Hospital, Dhaka. Patients who were presented with septic shock, pneumonia, very low birth weight and extreme prematurity, Anorectal malformation were excluded from the study. Result: Out of 196 patients, male patients were 135(68.87%), female 61(31.12%) and male to female ratio was 2.2:1. Most common cause of intestinal obstruction was Intestinal atresia 55(28.08%) followed by Hirschsprung disease 45(22.93%), Meconium ileus 43(21%), Malrotation of gut 23(11.73%), duodenal atresia 12 (6.12%), gastroschisis 10(5.10%) and other case 8(4.01%). Majority of neonates 158(80.61%) presented within 1st week of life and survival rate was 83.16%. Mortality in preterm was much higher 19(70.35%) than in term newborns 21(12.42%). Conclusion: Dedicated delicate neonatal surgical care, early diagnosis and intervention are the crucial factors in improving operative outcome in neonatal surgery. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 24-28